Studi Analisis Hadis tentang Niat Menurut Teori Hermeneutika Schleiermacher - Al-Maududi, Abdi; Ismail, Padli; Ridlo, Muhammad Abdurrasyid (Jurnal Penelitian Ilmu Ushuluddin, 2025)
The hadith of the prophet Muhammad SAW has a fundamental role in shaping the framework of values ​​and norms of Muslims. As the second source of Islamic law after the Qur'an, the Hadith is not only a reference in the theological realm, but also has relevance in various aspects of life. One of the most popular Hadith is "Innamal a'maalu bi niyyat" (Indeed, deeds depend on intentions). This Hadith is not only a guideline in assessing the validity of acts of worship, but also provides a philosophical meaning about motivation and integrity in human actions. However, the understanding of this Hadith is often limited to literal interpretation, which provides little room for adaptation in the ever-evolving social, cultural, and intellectual context. The purpose of this study is to determine the application of Schleiermacher's theory to the Hadith on intention, with a focus on the relationship between the language of the text, and the psychological conditions of the Prophet Muhammad SAW and his companions who conveyed the Hadith. This study will produce a more complete and comprehensive understanding of the meaning of the Hadith. This research method is qualitative with a literature study approach, data is collected through literary sources and analyzed using Schleiermacher's hermeneutic interpretation technique. The results of this study highlight how the intensity of grammatical and psychological dialogue in reading the hadith about Intention is relevant in social and cultural spaces. The conclusion of this study shows that reading the hadith about intention through Schleiermacher's hermeneutics can be submitted in more depth, not only focusing on the text as a linguistic product, but also on the historical context and the underlying purpose.